2021
DOI: 10.3389/fcell.2021.664327
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Hydrostatic Pressure Causes Retinal Degeneration Through Upregulating Lipocalin-2

Abstract: Elevation of intraocular pressure is a major risk factor for glaucoma development, which causes the loss of retinal ganglion cells (RGCs). Lipocalin 2 (Lcn2) is upregulated in glaucomatous retinae; however, whether Lcn2 is directly involved in glaucoma is debated. In this study, retinal explant cultures were subjected to increased water pressure using a two-chamber culture device, and Lcn2 protein levels were examined by immunoblotting. In situ TdT-mediated dUTP nick and labeling (TUNEL) and glial fibrillary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…A recent study using retinal explant cultures in a 2-chamber culture device indicated that LCN2 is directly involved in RGC death ( 40 ). It was further found, by exogenous administration of recombinant LCN2, that elevated LCN2 was neurotoxic to the retinal explant culture.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using retinal explant cultures in a 2-chamber culture device indicated that LCN2 is directly involved in RGC death ( 40 ). It was further found, by exogenous administration of recombinant LCN2, that elevated LCN2 was neurotoxic to the retinal explant culture.…”
Section: Discussionmentioning
confidence: 99%
“…Total 3 × 10 4 cells of NCI-H28, NCI-H2052, NCI-H2452, MSTO-211H, MESO-1, MESO-1-CADM1, MESO-14, and EHMES10 cells; 8 × 10 4 of MESO-4, MESO-8D, MESO-9 cells; 1 × 10 5 of MESO-12 cells; and 6 × 10 4 of MeT-5A cells were seeded onto a culture insert bottomed with a Matrigel-coated semipermeable membrane (Transwell, transparent PET membrane, pore size 0.4 μm; Falcon, Corning, Tokyo, Japan) placed in a 12-well plate. After 2 days, the cells cultured on a semipermeable membrane were reached 100% confluence and lysed in a buffer containing 50 mM Tris-HCl (pH 8.0), 150 mM NaCl, 1% Triton X-100 and 1 mM phenylmethylsulfonyl fluoride, and after removal of impurities by centrifugation, were subjected to Western blotting analyses as described in our previous report ( Hagiyama et al, 2020 ; Yoneshige et al, 2021 ). Immunoreactive band intensities were quantified using ImageJ software (National Institutes of Health, Bethesda, MD, United States), as described previously ( Mimae et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…[152,153] Elevated intraocular hydrostatic pressure has been linked to increased Lipocalin-2 (LCN-2) expression, which fosters tissue inflammation and mediates apoptosis and glial cell activation in retinal ganglion cells (RGCs), an effect that can be countered by desferrioxamine. [62] Additionally, NF𝜅B upregulation is closely associated with ferroptosis and inflammatory injury, potentially representing a new target for anti-iron and antioxidant interventions. [156] While inflammation plays a vital role in combating infection, aiding in pathogen clearance and tissue repair, it tends to exacerbate injury and promote tissue sclerosis in non-infectious pathologies associated with glaucoma.…”
Section: Challenges and Prospectivesmentioning
confidence: 99%
“…In DBA/2J mice models with secondary phIOP, a significant increase in lipocalin2 (Lcn‐2) content was observed, correlating with cell apoptosis and gliosis, indicating neurotoxicity. However, these adverse effects were mitigated by the iron chelator deferoxamine, [ 62 ] suggesting the involvement of iron‐dependent cell death. Cutting‐edge research, including in vitro and in vivo experiments with APACG patients, has revealed that retinal iron accumulation occurs abnormally within an 8‐h post‐damage period, mirroring changes in serum levels.…”
Section: Ferroptosis: Pre‐clinical Experiments In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation